Household adjustment to flood risk: a survey of coastal residents in Texas and Florida, United States. Issue 3 (22nd September 2016) - Brody, Samuel D.; Lee, Yoonjeong; Highfield, Wesley E.
Abstract : Individual households have increasingly borne responsibility for reducing the adverse impacts of flooding on their property. Little observational research has been conducted, however, at the household level to examine the major factors contributing to the selection of a particular household adjustment. This study addresses the issue by evaluating statistically the factors influencing the adoption of various household flood hazard adjustments. The results indicate that respondents with higher‐value homes or longer housing tenure are more likely to adopt structural and expensive techniques. In addition, the information source and the Community Rating System (CRS) score for the jurisdiction where the household is located have a significant bearing on household adjustment. In contrast, proximity to risk zones and risk perception yield somewhat mixed results or behave counter to assumptions in the literature. The study findings provide insights that will be of value to governments and decision‐makers interested in encouraging homeowners to take protective action given increasing flood risk.